Comparison of epiretinal membrane peel after dual staining versus en bloc peel using negative staining technique - Jahangir, Tehmina; Chaudhary, Qasim Latif; Tayyab, Haroon (Pakistan Journal of Ophthalmology, 2020)
Purpose: To compare the completeness of ILM peel in cases of Idiopathic Epiretinal Membranes following double staining and double peeling versus en bloc dissection of both using negative staining method. Study Design: Quasi experimental study. Place and Duration of Study: Jinnah Hospital Lahore, from October 2017 to March 2018. Material and Methods: Forty eyes of forty patients with Idiopathic Epiretinal membranes (ERM) were selected by non-probability convenient method and divided into two groups. In group A, the ERM was initially stained with Trypan blue and then peeled. Subsequently the macula was re-stained with Brilliant blue G (BBG). In group B, ERM and ILM were successfully peeled together as a single membrane utilizing the single block technique, after a desired negative staining effect was obtained by injecting BBG. The thoroughness of the ILM peel was established using another injection of BBG although a few remains were often identified outside the central macular area, no other dyes were used. Results: In group A, 8 of the 20 eyes (40%) had full undisturbed ILM present whereas in 10 eyes (50%) the ILM was there but damaged, only 2 eyes (10%) had near total ILM removed. In group B, the dual peeling was successful in 17 of the 20 cases (85%). There has been no recurrence of ERM until now. Conclusion: Instead of peeling twice, the single en bloc negative staining technique with Brilliant blue G is a safer and more effective method for removal of ERM together with ILM.